Sanguinett, J. J. Neurociencia y filosofía del hombre, Madrid, Ediciones Palabra, ISBN: 978-84-9061-111-1, pp. 391, 2014 - Donadío Maggi de Gandolfi, María C. (2015)
Fil: Donadío Maggi de Gandolfi, María C. Pontificia Universidad Católica Argentina; Argentina